2017
DOI: 10.1074/jbc.m117.794743
|View full text |Cite
|
Sign up to set email alerts
|

Cavin-2 regulates the activity and stability of endothelial nitric-oxide synthase (eNOS) in angiogenesis

Abstract: Angiogenesis is a highly regulated process for formation of new blood vessels from pre-existing ones. Angiogenesis is dysregulated in various pathologies, including age-related macular degeneration, arthritis, and cancer. Inhibiting pathological angiogenesis therefore represents a promising therapeutic strategy for treating these disorders, highlighting the need to study angiogenesis in more detail. To this end, identifying the genes essential for blood vessel formation and elucidating their function are cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(38 citation statements)
references
References 63 publications
2
35
0
1
Order By: Relevance
“…Cavin 2, a serum deprivation protein response gene, is enriched in lung tissue [12]. In this study, our data showed that low Cavin 2 expression was more easily observed in lung adenocarcinoma compared with normal lung tissues, indicating that Cavin 2 might be a tumor suppressor gene and Cavin 2 depletion might be implicated in the formation of lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Cavin 2, a serum deprivation protein response gene, is enriched in lung tissue [12]. In this study, our data showed that low Cavin 2 expression was more easily observed in lung adenocarcinoma compared with normal lung tissues, indicating that Cavin 2 might be a tumor suppressor gene and Cavin 2 depletion might be implicated in the formation of lung adenocarcinoma.…”
Section: Discussionsupporting
confidence: 51%
“…Unozawa et al reported that Cavin 2 up-regulation slowed cellular proliferation by regulating cell-cycle arrest in oral cancer [18]. Boopathy et al reported that Cavin 2 was required for endothelial cell proliferation, invasion and migration [12]. However, the effect of Cavin 2 expression on cell differentiation, proliferation, migration and invasion is still unclear in lung adenocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We anticipated a dramatic reduction in e-NO production as an outcome of decreased VEGFR2-e-NOS signaling in the absence of Agrin. Likewise, Agrin depletion severely hampered the production of e-NO, as measured by the formation of triazolo-fluorescein by NO indicator 4,5-diaminofluorescein diacetate (DAF-2-DA) (Boopathy et al, 2017;Govers et al, 2002) ( Figure 7F). The resulting inhibition of e-NO production and phospho-e-NOS status in Agrin-depleted HUVECs was comparable to that caused by treatment with N u -nitro-L-arginine-methyl ester hydrochloride (L-NAME), a known inhibitor for NO production (Boopathy et al, 2017) (Figure 7G).…”
Section: Agrin Controls Vegfr2-e-nos Signaling In Ecsmentioning
confidence: 99%
“…Likewise, Agrin depletion severely hampered the production of e-NO, as measured by the formation of triazolo-fluorescein by NO indicator 4,5-diaminofluorescein diacetate (DAF-2-DA) (Boopathy et al, 2017;Govers et al, 2002) ( Figure 7F). The resulting inhibition of e-NO production and phospho-e-NOS status in Agrin-depleted HUVECs was comparable to that caused by treatment with N u -nitro-L-arginine-methyl ester hydrochloride (L-NAME), a known inhibitor for NO production (Boopathy et al, 2017) (Figure 7G). The restoration of tube formation induced by soluble Agrin was blocked by L-NAME treatment in Agrindepleted HUVECs, suggesting that soluble Agrin required e-NO production to induce in vitro angiogenesis ( Figure S6C).…”
Section: Agrin Controls Vegfr2-e-nos Signaling In Ecsmentioning
confidence: 99%